The Influence of Work Motivation and Job Satisfaction on the Performance of Junior High School Teachers in West Aceh - Surya Darma Bakti; Syarfuni Syarfuni; Musdiani Musdiani (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to answer the problems of the two hypotheses proposed, namely the influence of work motivation on the performance of teachers at the West Aceh State Junior High School, the influence of job satisfaction on the performance of teachers at the West Aceh State Junior High School. The population of this study was 138 teachers. The research sample of 103 people was obtained by random sampling. The research instrument used a questionnaire with a Likert scale and the processing of research data was analyzed through the Statistical Package for the Social Sciences (SPSS) and path analysis. The results of the study showed that work motivation had a direct positive effect on the performance of teachers at the West Aceh State Junior High School, as shown by ?31 = 0.393 and the t count value> t table (2.081> 1.66) while the significance was 0.000 <0.050. 2) Job satisfaction had a direct positive effect on the performance of teachers at the West Aceh State Junior High School, as shown by ?23 = 0.500 and the t count value> t table (2.359> 1.66) while the significance was 0.000 <0.050. The implications of this study explain that work motivation and job satisfaction have a positive effect on teacher performance. This shows that teacher performance can be improved by increasing work motivation and job satisfaction.